Segmentación de células mediante técnicas de Procesamiento Digital de Imágenes para el rastreo de células cancerosas - Marín-Soto, David (Instituto Tecnológico de Costa Rica, 2018)
In recent years, the methodologies for cancerous cells identification in the microbiological scientific field, have been improving due to technological equipment insertion and the use of digital image processing and computer vision techniques. For such reason in Costa Rica, there is a project with important interest in cancerous cells tracking and analysis involving several institutions and public universities, including Instituto Tecnol´ogico de Costa Rica. Even though, there are absence of methods for cell image recognition; therefore, this graduation project is presented to be a first approach to allow further research and become a path for microbiologists goals. Finally, this project assess the impact of digital image processing applied as input for an automatic learning architecture, which is responsible for semantic segmentation of cancerous cells using computer vision techniques and deep learning.
Proyecto de Graduación (Licenciatura en Ingeniería Electrónica) InstitutoTecnológico de Costa Rica, Escuela de Ingeniería Electrónica, 2018.
Keywords: Aprendizaje; Células; Imágenes; Microbiología; Procesamiento; Segmentación; Research Subject Categories::TECHNOLOGY::Electrical engineering, electronics and photonics::Electronics